Application of the Pipeline Embolization Device for Giant Vertebrobasilar Dissecting Aneurysms in Pediatric Patients - Wang, Jiejun; Zhang, Yisen; Lv, Ming; Yang, Xinjian; Tian, Zhongbin; Liu, Jian; Liu, Peng; Miao, Zefeng; Jia, Luqiong; Chen, Junfan; Ding, Xinghuan; Zhang, Ying; et al. (Frontiers in Neurology, 2019)
OBJECTIVE: To evaluate the safety and effectiveness of the pipeline embolization device (PED) for the treatment of pediatric giant vertebrobasilar dissecting aneurysms (VBDAs). METHODS: We retrospectively reviewed our institutional clinical database and identified 2,706 patients who presented with a diagnosis of intracranial aneurysms from January 2016 to June 2018. Among this group, 153 patients were diagnosed with VBDAs, and 54 of these patients underwent PED therapy. The PED technique was used in four patients who were 18 years old or younger at the time of presentation (two males, two females; mean age 9.25 years; age range 8–11 years). RESULTS: All four included pediatric patients were managed with the PED. One patient (25%) was treated with the PED alone, while three (75%) were treated with the PED and coils. One patient died from brainstem infarction or compression of the brainstem, while follow-up of the other three patients revealed favorable outcomes. The mass effect was obviously reduced in cases 1, 2, and 3 on follow-up MRI performed 6 months after the PED procedure. CONCLUSIONS: PEDs could be feasible in treatment of pediatric giant vertebrobasilar dissecting aneurysms. However, its safety and efficacy have not been clarified in this special population, and the follow-up is still necessary.